The Bank's Efforts Against Mortgage Cases Over Building Utilization Rights Which Period Ends Before Financing Is Due - Titik Aminah (Badan Penerbit STIEPARI Press, 2022)
This journal is entitled Bank Efforts Against Building Use Rights Cases That Expire Before Financing is Due with the construction of the problem: 1. How is the legal arrangement by banks regarding cases of mortgages on building use rights whose period ends before financing is due; and 2. What are the obstacles and solutions from the bank in cases of mortgages on building use rights that expire before the financing is due. This journal's qualification/type of writing uses normative legal writing supported by sociological/empirical legal research. To analyze some of the problems in this journal, the prominent theory of legal positivism theory introduced by Jeremy Bentham as the Grand Theory is used. 1 This theory explains the pros and cons of law, which must be measured through a paradigmatic approach in legal theory. From the pros and cons of the consequences of applying the law itself. 2 Bentham tries to put forward the leading theory in one of his masterpieces which is described and constructed in such a way from an application of the law. 3 The author also conducts an analysis based on the legal theory introduced by John Austin, which is in line with Jeremy Bentham, where John Austin emphasized that the law is interpreted as an order from the legislator or ruler (as a command of the lawgiver). 4 This means, according to the author, all government officials working in the law enforcement field), including investigators at the Indonesian National Police, must carry out orders attributively from legislators or authorities in the provisions of the legislation.